Magnetic-sensor performance evaluated from magneto-conductance curve in magnetic tunnel junctions using in-plane or perpendicularly magnetized synthetic antiferromagnetic reference layers - T. Nakano; M. Oogane; T. Furuichi; Y. Ando (AIP Advances, 2018)
The automotive industry requires magnetic sensors exhibiting highly linear output within a dynamic range as wide as ±1 kOe. A simple model predicts that the magneto-conductance (G-H) curve in a magnetic tunnel junction (MTJ) is perfectly linear, whereas the magneto-resistance (R-H) curve inevitably contains a finite nonlinearity. We prepared two kinds of MTJs using in-plane or perpendicularly magnetized synthetic antiferromagnetic (i-SAF or p-SAF) reference layers and investigated their sensor performance. In the MTJ with the i-SAF reference layer, the G-H curve did not necessarily show smaller nonlinearities than those of the R-H curve with different dynamic ranges. This is because the magnetizations of the i-SAF reference layer start to rotate at a magnetic field even smaller than the switching field (Hsw) measured by a magnetometer, which significantly affects the tunnel magnetoresistance (TMR) effect. In the MTJ with the p-SAF reference layer, the G-H curve showed much smaller nonlinearities than those of the R-H curve, thanks to a large Hsw value of the p-SAF reference layer. We achieved a nonlinearity of 0.08% FS (full scale) in the G-H curve with a dynamic range of ±1 kOe, satisfying our target for automotive applications. This demonstrated that a reference layer exhibiting a large Hsw value is indispensable in order to achieve a highly linear G-H curve.